2013
DOI: 10.1192/bjp.bp.112.110999
|View full text |Cite|
|
Sign up to set email alerts
|

When the drugs don't work: the potential of glutamatergic antipsychotics in schizophrenia

Abstract: Currently available antipsychotic drugs target dopaminergic neurotransmission. Many patients do not respond fully to these treatments, and there has been considerable effort to investigate alternative targets. Here we summarise the rationale and recent evidence supporting efforts to develop glutamatergic antipsychotic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
(25 reference statements)
0
14
0
4
Order By: Relevance
“…More specifically, variations in corticostriatal association are seen in relation to treatment response in line with recent related findings (Sarpal et al, 2015); and striatonigral dysconnection is identified as a distinct feature of treatment-resistant illness. There is increasing interest in examining glutamatergic treatment options in schizophrenia (Papanastasiou et al, 2013) and elevated glutamate function has been observed in association with treatment resistance (Demjaha et al, 2014). Given recent accounts that the N-methyl-D-aspartate receptor antagonist, ketamine-which disinhibits glutamatergic stimulation of non-NMDA receptors (Moghaddam et al, 1997)-modulates functional connectivity of ventral striatum (Dandash et al, 2014), striatonigral disconnection is a viable mechanism for targeted treatment of refractory schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, variations in corticostriatal association are seen in relation to treatment response in line with recent related findings (Sarpal et al, 2015); and striatonigral dysconnection is identified as a distinct feature of treatment-resistant illness. There is increasing interest in examining glutamatergic treatment options in schizophrenia (Papanastasiou et al, 2013) and elevated glutamate function has been observed in association with treatment resistance (Demjaha et al, 2014). Given recent accounts that the N-methyl-D-aspartate receptor antagonist, ketamine-which disinhibits glutamatergic stimulation of non-NMDA receptors (Moghaddam et al, 1997)-modulates functional connectivity of ventral striatum (Dandash et al, 2014), striatonigral disconnection is a viable mechanism for targeted treatment of refractory schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Further, based on our present understanding, D 2 blockade forms the foundation of AP efficacy, at least in those who respond to currently available agents [116]. Although efforts continue to develop APs that effect their response through non-D 2 mechanisms [51,117], there are as of yet no such options. This is not to say we have not made gains.…”
Section: Expert Opinionmentioning
confidence: 97%
“…Innovative antipsychotic substances with novel mechanisms address the brain's glutamate system [111,112]. Among them, glycine-uptake inhibitors, NMDA receptor coagonists and agonists at the metabotropic glutamate receptors (mGlu) have been focused on [19].…”
Section: Agonists At the Metabotropic Glutamate Receptorsmentioning
confidence: 99%